Zinc Deficiency Blunts the Effectiveness of Antidepressants in the Olfactory Bulbectomy Model of Depression in Rats - Rafało-Ulińska, Anna; Pochwat, Bartłomiej; Misztak, Paulina; Bugno, Ryszard; Kryczyk-Poprawa, Agata; Opoka, Włodzimierz; Muszyńska, Bożena; Poleszak, Ewa; Nowak, Gabriel; Szewczyk, Bernadeta (Nutrients, 2022)
Currently used antidepressants do not always provide the desired results, and many patients suffer from treatment-resistant depression. Clinical studies suggest that zinc deficiency (ZnD) may be an important risk factor for depression and might blunt the effect of antidepressants. This study aimed to examine whether ZnD might blunt the effectiveness of antidepressants in the olfactory bulbectomy model (OB) of depression in rats. For this purpose, rats were subjected to the OB model, fed a zinc-deficient diet (3 mg Zn/kg) for 3 weeks, and finally treated with escitalopram (Esc), venlafaxine (Ven) 10 mg/kg, i.p., or combined Esc/Ven (1 mg/kg, i.p.) with zinc (5 mg/kg) for another 3 weeks. Open field (OFT), forced swim (FST), and sucrose intake (SIT) tests were used to evaluate depressive-like behavioral changes. In addition, serum, intracellular, and synaptic Zn concentrations and the level of zinc transporter (ZnT) proteins were analyzed. The OB + ZnD model induced hyperactivity in rats in the OFT, increased immobility time in the FST, and anhedonia in the SIT. Chronic treatment with Esc reduced immobility time in the FST in the OB + ZnD model. Esc/Ven +Zn increased sucrose intake in rats from the OB + ZnD group. The OB + ZnD decreased serum zinc levels and intracellular and synaptic Zn concentration in the prefrontal cortex (PFC) and cerebellum. These changes were normalized by chronic administration of Esc/Ven +Zn. Moreover, OB + ZnD decreased levels of the ZnT1 protein in the PFC and Hp and ZnT3 in Hp. Chronic administration of antidepressants did not alter the levels of ZnT proteins. The OB + ZnD model induces more depressive-like effects than either model alone. Our results show that ZnD may induce drug resistance in rats. Normalizing serum or brain zinc concentration is insufficient to reverse behavioral abnormalities caused by the OB + ZnD model. However, zinc supplementation might improve the effectiveness of antidepressants in reversing particular depression symptoms.